Impact of deviations in target volume delineation – Time for a new RTQA approach?. (August 2019) - Cox, Samantha; Cleves, Anne; Clementel, Enrico; Miles, Elizabeth; Staffurth, John; Gwynne, Sarah
Highlights: Few trials have published outcomes on the clinical impact of TVD protocol deviations. Unacceptable deviations must be clearly defined to minimise interobserver variation. Trials involving novel/complex RT techniques should implement prospective TVD reviews. Evidence-base needed through consistent recording and reporting of RTQA programmes. Abstract: The international radiotherapy community has recognised that non-adherence to RT protocols can influence trial endpoints. However this conclusion is based on studies predominantly assessing the impact of deviations in dosimetric or treatment delivery protocol parameters rather than target volume delineation (TVD). This review evaluates the assessment of TVD within Radiation Therapy Quality Assurance (RTQA) programmes in clinical trials and the clinical impact of TVD protocol deviations. The implications for RTQA programmes are discussed. MEDLINE, PreMEDLINE, Embase, Cochrane Library, Web of Science, OpenGrey, WHO International Clinical Trials Registry Platform portal andClinicalTrials.gov were searched. Full-length articles and conference abstracts were included to avoid publication bias. 5864 abstracts were screened for relevance; 94 full-length articles were reviewed and 5 relevant trials identified. Various classification systems were used to assess protocol deviations; 'unacceptable' or 'major' deviations in TVD occurred in 2.9–13.4% of assessed RT plans (when reported). It was often not possible to establish deviation rates specifically related to TVD as these were frequently combined with other types of protocol deviations. Details on the nature of unacceptable deviations was also not routinely reported and difficulties in establishing a 'consensus' for appropriate TVD for on-trial patients highlighted. Results suggest that deviations in TVD were associated with poorer outcomes for overall survival, local control and treatment-related toxicity; however the data were heterogeneous. RTQA of TVD was retrospective and feedback on the quality of TVD to recruiting centres was not standard. In summary, few trials have published outcomes on the impact of assessing the quality of TVD in trials. We propose that a new approach is now required. Unacceptable TVD deviations must be clearly defined at the time of protocol development to minimise interobserver variation, thereby promoting consistency in RTQA feedback. Prospective TVD reviews should be implemented for trials involving novel or complex RT techniques to identify deviations that require modification prior to treatment delivery. Furthermore, the consistent reporting of RTQA programme outcomes, both within and across trial groups, is of paramount importance to accelerate the evidence-base for the best RTQA approach when assessing TVD and to enable the impact on clinical outcomes within RT trials to be assessed.